Identification and Characterization of Quorum-Quenching Activity of N-Acylhomoserine Lactonase from Coagulase-Negative Staphylococci - Tomohiro Morohoshi; Yaoki Kamimura; Nobutaka Someya (MDPI AG, 2020)
N-Acylhomoserine lactones (AHLs) are used as quorum-sensing signals in Gram-negative bacteria. Many genes encoding AHL-degrading enzymes have been cloned and characterized in various microorganisms. Coagulase-negative staphylococci (CNS) are present on the skin of animals and are considered low-virulent species. The AHL-lactonase gene homologue, ahlS, was present in the genomes of the CNS strains Staphylococcus carnosus, Staphylococcus haemolyticus, Staphylococcus saprophyticus, and Staphylococcus sciuri. We cloned the candidate ahlS homologue from six CNS strains into the pBBR1MCS5 vector. AhlS from the CNS strains showed a higher degrading activity against AHLs with short acyl chains compared to those with long acyl chains. AhlS from S. sciuri was expressed and purified as a maltose-binding protein (MBP) fusion. Pseudomonas aeruginosa is an opportunistic pathogen that regulates several virulence factors such as elastase and pyocyanin by quorum-sensing systems. When MBP-AhlS was added to the culture of P. aeruginosa PAO1, pyocyanin production and elastase activity were substantially reduced compared to those in untreated PAO1. These results demonstrate that the AHL-degrading activity of AhlS from the CNS strains can inhibit quorum sensing in P. aeruginosa PAO1.